Legal Certainty of Marriage Agreements Made Before Marriage and Their Implications After Divorce - Alvira Damayanti; Yunanto (Fakultas Hukum, Universitas Warmadewa, 2024)
The dissolution of a marriage results in legal consequences, one of which is the division of joint assets in the marriage. Property law in marriage is regulated in Articles 35 to 37 of the Marriage Law Number 1 of 1974. The Marriage Law allows both prospective husband and wife to make a marriage agreement to separate property. The marriage agreement that is made causes the agreement to become valid as law for both parties who make it. Regarding this problem, the author is interested in researching how legal certainty is regarding marriage agreements made before marriage in relation to joint property and what the legal consequences are for marriage agreements that are not in accordance with the marriage agreement when a divorce occurs. The theories used are the theory of legal certainty from Gustav Radbruch and the theory of agreement from Subekti. The method used in this research is a type of normative juridical research, namely legal library research or secondary data with primary, secondary and tertiary sources of legal materials. The research approaches used are the statutory approach, conceptual approach, analytical approach, case approach, historical approach and legal material collection techniques carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal material. The analysis technique for legal materials is carried out using legal interpretation (interpretation), namely, historical interpretation, systematic interpretation, teleological interpretation and legal construction methods. From the research results, it can be concluded that the marriage agreement made still has legal certainty because it does not violate the law and the marriage agreement is included in the law for both parties in accordance with Article 1338 of the Civil Code. The legal consequences of marriage regarding joint property in the event of a marriage agreement are regulated in Article 37 of the Marriage Law, the distribution of which is according to the agreement made.